Electroconvulsive shock increases the behavioural responses of rats to brain 5-hydroxytryptamine accumulation and central nervous system stimulant drugs. - Evans, J P (1976)
1 A single electroconvulsive shock (ECS) of 150 V for 1 s increased the concentration of rat brain 5-hydroxyindoleacetic acid (5-HIAA) but did not alter brain 5-hydroxytryptamine (5-HT) or tryptophan concentrations 3 h later. 2 A single ECS decreased 5-HT synthesis 3 h and 6 h later. Synthesis was back to normal after 24 hours. The ECS-treated rats did not show greater hyperactivity produced by the increased brain 5-HT accumulation following administration of L-tryptophan and tranylcypromine at any time up to 24 h later. This suggests that a single electroshock does not alter 5-HT functional activity. 3 Twenty-four hours after the final ECS of a series of 10 shocks given once daily, the rats were given tranylcypromine and L-tryptophan. They displayed greater hyperactivity than control rats not treated with ECS, suggesting that ECS increases 5-HT functional activity. Brain concentrations of 5-HT, 5-HIAA and tryptophan were then unchanged by ECS. 5-HT synthesis and accumulation of 5-HT following tranylcypromine and L-tryptophan were not altered by ECS. 4 The hyperactivity following administration of the 5-HT agonist 5-methoxy N,N-dimethyltryptamine was enhanced by repeated (10 day) ECS, suggesting altered post-synaptic responses to 5-HT receptor stimulation. 5 Repeated ECS enhanced locomotor activity following tranylcypromine and L-DOPA. It did not alter brain noradrenaline or dopamine concentrations. 6 The latent period before a pentylenetetrazol-induced convulsion was shortened by repeated ECS. 7 Following repeated ECS there appears to be increased neuronal sensitivity to certain stimuli producing centrally mediated behavioural stimulation. This is discussed in relation to the mechanism by which electroconvulsive therapy (ECT) produces its therapeutic effect.